Influenza vaccine is able to induce post-infection antibodies to SARS-CoV-2 in medical staff - M. P. Kostinov; N. Yu. Nastaeva; N. F. Nikityuk; N. K. Akhmatova; M. I. Albahansa; S. V. Yushkova; N. P. Andreeva; A. M. Kostinova; A. V. Linok; M. N. Loktionova; I. A. Khrapunova (Медицинская иммунология)
Influenza vaccination contributes to the favorable course and outcome of COVID-19. The aim of our study was to study the effect of influenza and pneumococcal vaccines on the level of IgG antibodies (AT) to SARS-CoV-2 among medical personnel at the beginning of the COVID-19 pandemic. We present the data on assessment of specific immune response to the influenza virus and SARS-CoV-2 in 266 medical workers 6 months after immunization against influenza and/or pneumococcal infection (without vaccinations against COVID-19) over the 2020-2021, by comparing the results with respective characteristic in 281 employees with no history of vaccinations is presented.We have found that the proportion of medical workers with a protective (≥ 1:40) antibody levels to influenza virus 6 months after vaccination in groups of participants reaches a protective (≥ 70%) value only in persons who received a monovaccine against pneumococcal infection (78.6%) as compared with persons vaccinated with a monovaccine against influenza (61.7%) (p < 0.001), as well as with a group of workers immunized against influenza in combination with the S. pneumoniae vaccine (68.9%) (p < 0.01). Hence, the pneumococcal vaccine is able to induce the synthesis of IgG-AT to influenza virus reaching protective values.An analysis of the group with seropositivity to influenza virus (IgG-AT ≥ 1:10) and their comparisons with persons seroprevalent to COVID-19 showed that the proportion of seropositive individuals among medical staff vaccinated against seasonal influenza after 6 months (indicating a probable asymptomatic form of COVID-19) is increased. It comprised 65.4% (p = 0.026) in the group vaccinated with mono-flu, and 64.5% (p = 0.04) in the group vaccinated with combined influenza and pneumococcus, being higher than among the non-immunized workers (48.8%).In summary, the results of our study show that influenza vaccination acts as an inducer of humoral immunity not only to the influenza virus, but also to the recently transmitted SARS-CoV-2 infection.